PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA LUMER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 167 SEBERANG KECAMATAN LAMURU KABUPATEN BONE - fuadi, nurul; muliadi, muliadi; sudirman, sudirman (Sains Global Institut, Indonesia, 2025)
This research is a class action research that aims to find out how the application of the Team Games Tournament (TGT) learning model assisted by Lumer media to improve social studies learning outcomes of fourth grade students of SD Negeri 167 Seberang, Lamuru District, Bone Regency. The approach used in this research is descriptive qualitative. The subjects in research study were all 27 class IV students and the class IV homeroom teacher. Data collection techniques using observation and tests. Data analysis techniques in this study are reducing data, describing data and drawing conclusions. The results showed that in the first cycle as many as 66.67% or 18 students obtained an average score of 74% and experienced in second cycle as many as 81.48% or 22 students with an average score of 80%. It can be concluded that the Team Games Tournament (TGT) learning model assisted by Lumer media can improve students' social studies learning outcomes.